Distributed computer and communication networks 22nd International Conference, DCCN 2019, Moscow, Russia, September 23-27, 2019, Revised Selected Papers /: 22nd International Conference, DCCN 2019, Moscow, Russia, September 23-27, 2019, Revised Selected Papers. (c2019) - Unknown
No abstract available